Estágio docente na formação de professores para o Ensino de Ciências na Amazônia - Pereira, Waldileia do Socorro Cardoso (2009)
This work is result of research realized at Profissional Master’s degree in Amazon Science Teaching at Amazon University of State. The general objective, was make analyses upon teachers training process in 2006 and 2007 classroom. The pretension is contribute to teachers’ formation at Amazon Science teaching master degree. Others objectives that orientated the research was: 1) to discuss about the development and organization of Pós-graduate in Science teaching at the Amazon observing the structure of master degree course in Science Teaching; 2) To reflect about the formation process and teachers training at master degree punctuating difficult and possibility in construction process of knowledge necessary for university pedagogy; 3) to discuss about people defined for research, conception of university, Pósgraduation, teachers training and pedagogical practice thus remarking the students supervised teaching practice report. The problematic source is the student’s process of knowledge construction including all elements present at teachers training moment and its relations, especially for the students that are not graduated in Science. This is qualitative analyses and we try to see the problem in differents dimensions with its relations between facts and people defined for the research. The subject is justified for its importance for teachers identify construction. Turn evident the possibility and necessity of constant dialogue between scientific knowledge produced in the university and what we live outside as people in constant historic formation process. Is a fact that we are habituated with work, survival, feelings and knowledge trying “to be more”. The result of this investigation is a proposal that introduce a equivalence between the disciplines for teachers training and his initial formation, this can possibility a re-signification of theorist and technical knowledge preparing the teachers for the university pedagogy.